Ways of escape : modern transformations in leisure and travel / Chris Rojek - Rojek, Chris
But popular culture venerates leisure and travel as authentic escape routes from routine and monotony. A major scholarly contribution to the sociological analysis of leisure, pleasure and travel, Dr Rojek's study is a radical challenge to the existing paradigmatic orthodoxy.